Sexual selection on forelimb muscles of western grey kangaroos (skippy was clearly a female) - Warburton, N.; Bateman, Bill; Fleming, P. (Wiley-Blackwell Publishing Ltd, 2013)
Studies of sexual selection have tended to concentrate on obvious morphological dimorphisms such as crests, horns, antlers, and other physical displays or weapons; however, traits that show no obvious sexual dimorphism may nevertheless still be under sexual selection. Sexual selection theory generally predicts positive allometry for sexually selected traits. When fighting, male kangaroos use their forelimbs to clasp and hold their opponent and, standing on their tail, bring up their hind legs to kick their opponent. This action requires substantial strength and balance. We examined allometry of forelimb musculature in male and female western grey kangaroos (Macropus fuliginosus) to determine whether selection through male-male competition is associated with sex differences in muscle development. Forelimbs of males are more exaggerated than in females, with relatively greater muscle mass in males than the equivalent muscles in females. Furthermore, while muscles generally showed isometric growth in female forelimbs, every muscle demonstrated positive allometry in males. The significant positive allometry in male forelimb musculature, particularly those muscles most likely involved in male-male combat (a group of muscles involved in grasping: shoulder adduction, elbow flexion; and pulling: arm retraction, elbow flexion), clearly suggests that this musculature is subject to sexual selection. In addition to contributing to locomotion, the forelimbs of male kangaroos can also act as a signal, a weapon, and help in clasping, features that would contribute towards their importance as a sexually selected trait. Males would therefore benefit from well-developed musculature of the arms and upper body during competition for mates.